The Role of Task-Specific Response Strategies in Blocked-Cyclic Naming - Belke, Eva (Frontiers in Psychology, 2017)
In word retrieval, speakers need to select a lexical entry among several co-activated candidates for lexicalization. How a target entry is selected is a matter of ongoing debate. Semantic context effects on naming times, as seen in the blocked-cyclic naming paradigm, are of specific interest to this debate. In the standard version of this paradigm, participants name lists of objects compiled from several repetitions (cycles) of a small set of semantically related objects (homogeneous context) or unrelated objects (heterogeneous context). In the first cycle, participants typically show either no context effect or semantic facilitation. From cycle two onwards, they display a stable semantic interference effect that does not increase over cycles. In this review, I demonstrate that the early semantic facilitation effect is only observed consistently in studies that present homogeneous and heterogeneous lists in a blocked fashion. With this design, participants can easily pick up on the categorical relatedness of the items in semantically related contexts and apply this knowledge strategically. In principle, such response strategies can be easily tied in with existing models of lexical selection, but they are incompatible with accounts of semantic context effects that take the semantic facilitation effect in cycle 1 to be a consequence of processes inherent to the lexicalization process. Users of the blocked-cyclic naming paradigm should review their experimental designs carefully regarding potential response strategies. Once these are taken into account, the paradigm can be used to study lexical-semantic encoding in different populations of healthy and also impaired speakers.